2015
DOI: 10.1080/09647775.2015.1044461
|View full text |Cite
|
Sign up to set email alerts
|

Telling migrant stories in museums in Australia: Does the community gallery still have a role to play?

Abstract: This article examines the challenges associated with collecting and exhibiting objects to represent immigration history. We consider a range of Australian museums, from large federal institutions, for example, the Australian National Maritime Museum (ANMM), to state-based organisations such as the Immigration Museum (IM, Victoria) and the Migration Heritage Centre (MHC, New South Wales), as well as smaller communitybased and council-run museums like Hurstville City Library Museum and Gallery and Fairfield City… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…This choice of form is perhaps unsurprising, given that diasporic, migrant and refugee communities have long sought to establish museums or organize exhibitions that document the trauma of lost homeland and invite empathy from their potential audiences, while also seeking to communicate a narrative of hope and success in a new home (Loutron et al, 2020). Research on community museums and galleries has shown that the establishment of this type of space is evidence of the vested interests that groups have in claiming and documenting their own history and celebrating their place in society by using the dominant cultural format of the museum (O’Reilly and Parish, 2015). Mora Simpson (2001) identifies this trend as an international movement where communities have ‘become much more actively involved in the process of making representations and turned the focus upon those who, in the past, were so often neglected by collectors and curators of social history’ (p. 71).…”
Section: The Characteristics Of the Kresy-siberia Virtual Museum And ...mentioning
confidence: 99%
“…This choice of form is perhaps unsurprising, given that diasporic, migrant and refugee communities have long sought to establish museums or organize exhibitions that document the trauma of lost homeland and invite empathy from their potential audiences, while also seeking to communicate a narrative of hope and success in a new home (Loutron et al, 2020). Research on community museums and galleries has shown that the establishment of this type of space is evidence of the vested interests that groups have in claiming and documenting their own history and celebrating their place in society by using the dominant cultural format of the museum (O’Reilly and Parish, 2015). Mora Simpson (2001) identifies this trend as an international movement where communities have ‘become much more actively involved in the process of making representations and turned the focus upon those who, in the past, were so often neglected by collectors and curators of social history’ (p. 71).…”
Section: The Characteristics Of the Kresy-siberia Virtual Museum And ...mentioning
confidence: 99%
“…In the case of heART space , the youth involved had lived experience with grief, drug use and homelessness, which positioned them as drivers of the project. In smaller galleries or museums where full collaboration is possible, these spaces can foster a sense of community (Crooke, 2007; O’Reilly and Parish, 2015; Robertson and Gregory, 2018). Collaborative project development can build both a sense of agency and solidarity amongst community, particularly when members have control over the outcome of the project.…”
Section: Collaborating As Carementioning
confidence: 99%
“…This situation has been debated over the last few decades in relation to the place of community exhibitions in national and other large public museums that seek to be representative of a broad and diverse national cohort. The concern here is that community exhibitions 'cycle' through communities, which are represented for a short while and then disappear again (O'Reilly and Parish 2015;Message 2006).…”
Section: Scoping the Fieldmentioning
confidence: 99%